Merdeka Belajar Kampus Merdeka and the Development of English for a Specific Purpose Book - Diana Oktavia; Nur Habibah (Indonesian Research Journal in Education |IRJE|, 2022)
This research aimed to develop English for a specific purpose book: Merdeka Belajar Kampus Merdeka based. This book is made following indicators of Kampus Merdeka policy, where the students become the center of the class. This book provides some projects and cases that should be finished by the students related to the materials to fulfill the indicators. This developed book was validated by content experts’ validators and media experts’ validators. The validation used a content questionnaire and a media questionnaire. Based on the results, this book is validated and can be used as teaching and learning materials in English for a specific purpose. Both validators gave scores that were categorized as good, which was more than 50%. Furthermore, based on the trial, the first and second observations were categorized as very good. They were 80% at the first observation and 87,5% at the second observation.